Human-made. Waste as a resource for urban regeneration in Jabal al Jofeh refugee camp - Noor Marji; Janset Shawash; Narmeen Marji (Agathón, 2021)
The paper deals with the use of waste as a resource for urban regeneration and social integration of marginalised communities in Amman (Jordan) through the case study of the Jabal al Jofeh refugee camp, a poor ‘informal’ area with a Palestinian refugee population characterised by high crime, unemployment and poverty rates. The proposed Urban Regeneration Plan focuses on the use and reuse of accumulated waste as construction material and on the creation of a neighbourhood network for the collection, sorting and recycling of waste and its transformation into saleable products that generate income for the community. The vulnerable area of the camp is thus transformed into an active connection with the culturally rich historic centre of Amman through a human-centred approach to urban design and planning, creating a sustainable micro-economy with people as its main resource.